Perfil epidemiológico dos pacientes atendidos com anomalias da diferenciação sexual em serviço de referência na região norte do Brasil no período de 2006 à 2018 - SILVA, Joissilane Rodrigues da (2023)
INTRODUCTION: Anomalies of sexual differentiation (ADS) are characterized by the occurrence of an atypical development of chromosomal, gonadal or anatomical sex. It concerns cases of genital ambiguity, these are usually observed soon after birth, as it is not possible to identify the external genitalia as male or female. Requiring a quick investigation and at the same time needs to involve professionals from different areas. OBJECTIVES: This study aimed to analyze the clinical and epidemiological aspects of sexual differentiation anomalies in patients attended at a referral hospital in the state of Pará from 2006 to 2018. METHOD: This is a descriptive, retrospective observational study. RESULTS: From the present study identified a total of 60 cases of ADS, a frequency of 20% of disease in the population referred for investigation in this service, most children did not have birth registration with identification of sex (38.33%), were in the first year of life (53.33%), from the interior of the state of Pará or other states (53.33%), with karyotype 46, XX (46.67%), having as main manifestations for the karyotype Congenital adrenal hyperplasia (38.33%) and disorders of gonadal determination (30.00%) for karyotype 46, XY, located mainly between stages 3 and 5 of Prader (68.33%), revealed that 14 patients (23.33%) had a history of ADS in the family and 15% reported having used some medication during pregnancy. About 60% of the children were diagnosed in the delivery room, 68.33% reported by the doctor, a little more than 61% of the parents registered their children even without an investigation, only 16.66% had care at the reference center until the 28 days of birth. Taking as a research bias, the deficiency of a computerized service in the outpatient services in the reference service and lack of some data recorded in the medical records. CONCLUSION: The frequency of cases was considered high when compared to the other studies. Most were from the interior of Pará and other states. The most associated risk factors were medication use during pregnancy and cases of ADS in the family. The time in which a child born with ADS took to the realization of the first consultation in the service was in average of 2 years and 8 months. The most frequent nosological entity was congenital adrenal hyperplasia.